A Study on Needs Assessment of Infection Control Practices at A District Hospital in Southern India, Using Kayakalp Tool - Parvathy T Somaiah; Shivaraj B Mallappa (Medsci Publications, 2016)
Background: Mortalities and morbidities due to hospital acquired infections are rising in alarming numbers. As a part of Swachh Bharat Abhiyaan campaign, the Ministry of Health and Family welfare launched "Kayakalp", an initiative to promote cleanliness and enhance the quality of public health facilities. The study was done to assess of Infection control practices in Government District hospital at Madikeri using Kayakalp tool. Material and methods: A cross sectional study was conducted by using the Kayakalp assessment tool at District hospital Madikeri during September 2015. Results: The assessment using the tool showed the infection control practices in the hospital are poor and not adequate. The assessment showed the following results: hand hygiene practices (30%), use of personal protective equipments( 40%) and personal protective practices( 70%), decontamination and cleaning of instruments( 50%), disinfection and sterilization of instruments (80%), Spill management( 30 %), isolation and barrier nursing( 90%), hospital infection control program(50%), hospital acquired infection surveillance( 0%) and environmental control( 60%). Overall, the hospital scores 50% in infection control practices. Conclusion: Hospital acquired infection is commonest complication seen in any hospitalized patient. Simple basic preventive measures like hand hygiene and use of personal protective equipments among healthcare personnel can reduce the incidence and prevalence of these infections.